Proses Fonologis pada Prefiks /me-/ dalam Bahasa Indonesia - Dewi Rosnita Hardiani (Faculty of Economics, Law, and Humanities, 2019)
The purpose of this article is to describe the phonological process in the prefix /me-/ in Indonesian especially on the morphophonemic aspects. Morphonemic can be interpreted as a new word formation process. This process must be seen from the point of view of phonology and morphology. Phonological aspects play an important role in the morphophonic process where distinctive features are used to present the results. This paper used transformational generative phonological theory. The method used a qualitative descriptive approach. The results of the analysis show that the phonological process that occurs in morphophonemic prefixes / me- / in Indonesian is the addition of consonants and also assimilation of consonant-vowels Keywords: prefix /me-/, morphophonemic, distinctive features